2022
DOI: 10.1159/000522575
|View full text |Cite
|
Sign up to set email alerts
|

Matrix-Bound Nanovesicles: What Are They and What Do They Do?

Abstract: Over the past 50 years, several different types of extracellular vesicles have been discovered including: exosomes, microvesicles, and matrix vesicles. These vesicles are secreted by cells for specific purposes and contain cargo such as micro-RNA, cytokines, and lipids. A novel extracellular vesicle, the matrix bound nanovesicle (MBV), has been recently discovered. The MBV is similar to the microvesicle however, it is attached to the extracellular matrix, instead of being secreted. This review compares MBVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 125 publications
2
10
0
Order By: Relevance
“…MBVs are a subclass of extracellular vesicles (EVs), which range in size from 20 to 400 nm. They are distinguished from other EVs because they are found tightly adhering to the collagen network of ECM and because they have tissue-specific surface markers and cargo content, which includes lipids, proteins, signalling cytokines and chemokines, and nucleic acids [23][24][25][26]. These contents seem to greatly contribute to the immunomodulatory potential of dECM biomaterials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…MBVs are a subclass of extracellular vesicles (EVs), which range in size from 20 to 400 nm. They are distinguished from other EVs because they are found tightly adhering to the collagen network of ECM and because they have tissue-specific surface markers and cargo content, which includes lipids, proteins, signalling cytokines and chemokines, and nucleic acids [23][24][25][26]. These contents seem to greatly contribute to the immunomodulatory potential of dECM biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…In different studies, MBVs, even when isolated from different tissue sources, have shown the ability to recapitulate the immunomodulatory and regenerative potential of dECM, and have been successfully used both in vitro and in vivo for different regenerative medicine applications, suggesting their vast potential for biomedical applications [27][28][29][30][31][32][33][34]. Even though MBVs seem to be a ubiquitous component of the ECM, maintained even after the tissue decellularisation process, to date, they have only been isolated from small intestine submucosa, urinary bladder matrix, dermis, brain, oesophagus, heart, muscle, liver, ovary, pancreas, and tendons [23][24][25]35]. The research characterising these MBVs has shown that there are slight differences in the cargo, surface markers, and, thus, biological potential, of each tissue-specific MBV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicles (EVs) are lipid bilayer structures secreted by living cells and are classified into either exosomes, microvesicles (MVs), or apoptotic bodies, based on the intracellular production mechanism and size ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , …”
Section: Introductionmentioning
confidence: 99%